Idiopathic Granulomatous Mastitis Associated with Erythema Nodosum - Tuğba Özlem Kalaycı; Melike Bedel Koruyucu; Melda Apaydın; Makbule Varer; Demet Etit (Balkan Medical Journal, 2016)
Background: Idiopathic granulomatous mastitis (IGM) is an uncommon benign chronic inflammatory breast disease, and erythema nodosum (EN) is an extremely rare systemic manifestation of IGM. Here, we report a rare case of IGM accompanied by EN.